Effects of height-induced postural threat on static and dynamic balance performance in healthy individuals: a systematic review with meta-analysis - Wissmann, Anna Maria; Muehlbauer, Thomas; Hill, Mathew W. (Frontiers in Human Neuroscience, 2025)
BackgroundHeight-induced postural threat, such as standing or walking at elevation, elicits fear-related adaptations in balance control. Understanding these adaptations is crucial for interpreting motor behavior under anxiety and for informing rehabilitation and fall-prevention interventions. However, no previous systematic review with meta-analysis has quantified how height exposure influences balance performance.ObjectiveThe objective was to aggregate, characterize, and quantify the effects of height-related postural threat on static and dynamic balance performance.MethodsA systematic literature search in the electronic databases PubMed, Web of Science, and SPORTDiscus was conducted from their inception date until 15 September 2025. Eligible cross-sectional studies compared ground-level (no threat) versus elevated (threat) conditions in healthy participants. Static balance outcomes during upright stance included sway amplitude and frequency; dynamic balance outcomes while walking included gait velocity. Included studies were coded for gender, age, postural threat conditions, balance assessment/outcome, and test modality. Methodological study quality/design and risk of bias was assessed using the Appraisal tool for Cross-Sectional Studies. Heterogeneity was quantified using I2 statistics, and sensitivity was evaluated via Leave-One-Out method. Standardized mean differences (SMD) were calculated and analyses were stratified by age group (i.e., children, young adults, older adults).ResultsThe search identified a total of N = 438 records, and 25 of them (involving a total of 877 participants) met the inclusion criteria. Concerning static balance (18 studies, 44 comparisons), postural threat resulted in small-sized (SMD = 0.20) decreases in sway amplitude measures and in large-sized (SMD = 1.06) increases in sway frequency measures, indicating a potentially protective “stiffening” response. However, children did not use the “stiffening” response when standing at height (sway amplitude: SMD = −0.41; sway frequency: SMD = −0.04). Regarding dynamic balance (7 studies, 16 comparisons), postural threat led to large-sized (SMD = 1.33) declines in gait velocity, and this was more pronounced for conditions with a high (SMD = 1.78) than a low (SMD = 1.05) difficulty level.ConclusionHeight-induced postural threat evoked functional changes in static (i.e., decrease/increase in sway amplitude/frequency measures) and dynamic (i.e., decrease in walking speed measures) postural control. For static balance this is indicative of an effective “stiffening” response which is apparently not yet developed in children. For the dynamic balance, the further decrease in gait velocity during difficult walking conditions at height implies a compensatory mechanism to increase stability. Despite consistent direction and magnitude of effects, substantial between-study heterogeneity limits the generalizability of these findings, and results should therefore be interpreted with caution.